A Chaotic Maps-Based Authentication Scheme for Wireless Body Area Networks. (14th July 2016) - Gao, Gaimei; Peng, Xinguang; Tian, Ye; Qin, Zefeng
As a technology of monitoring and recording human body health signals, wireless body area networks (WBANs) play an increasingly important role in the field of healthcare. Inspired by the semigroup property of Chebyshev maps, we designed a novel chaotic maps-based authentication scheme for wireless body area networks. The study aims to avoid modular exponential computation or scalar multiplication on an elliptic curve and reduce the need for time-consuming. Compared with the previous schemes, our scheme not only enjoys more security features but also has reduced computational cost of client and application provider. Moreover, we present the security model for our scheme, demonstrate the validity of the protocol by the BAN (Burrows, Abadi, and Needham) logic in detail, and analyze the software implementation method of Chebyshev polynomial.